2018
DOI: 10.1111/eci.13009
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of coronary heart disease or heart failure using high‐sensitivity cardiac troponin T: A pilot study

Abstract: The majority of patients with hs-cTnT above the 99th percentile did not have structural heart disease or ischaemic coronary disease. However, 30% of the patient did have signs of coronary disease and might benefit from preventive medical treatment. Measuring hs-cTnT in the absence of acute illness might be a better approach for evaluation for sub-clinical cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Elevated troponin values suggest myocardial damage, which can be seen in acute myocardial infarction, unstable angina, pulmonary infarction, and heart failure. Our findings are consistent with those of a pilot study 31 and a cohort study 32 reporting hs-TnT as a good prognostic marker for mortality. Moreover, hs-TnT can be used to detect subclinical cardiac disease.…”
Section: Discussionsupporting
confidence: 92%
“…Elevated troponin values suggest myocardial damage, which can be seen in acute myocardial infarction, unstable angina, pulmonary infarction, and heart failure. Our findings are consistent with those of a pilot study 31 and a cohort study 32 reporting hs-TnT as a good prognostic marker for mortality. Moreover, hs-TnT can be used to detect subclinical cardiac disease.…”
Section: Discussionsupporting
confidence: 92%
“…It was found that the patients in observation group had obviously lower LVESV, LVEDV, and LVEF than the Ctrl (P < 0.05), and LVESD, LVEDD, CO, and CI were obviously higher (P < 0.05). LVESV, LVEDV, LVEF, LVESD, LVEDD, CO, and CI indicators are important indicators used to evaluate the volume, shape, function, and structure of the heart [20]. It was found that Shexiang Baoxin pills could reduce the left ventricular volume, increase the left ventricular inner diameter, and improve the heart function by increasing cardiac output and enhancing cardiac systolic function.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of troponin C isoform existing in both cardiac and skeletal muscle makes it not be considered as a sensitive marker of cardiac injury. However, the myocardium speci c troponin I and T is an useful biomarker for myocardial necrosis and has been clinically used for early diagnosis and prognosis in patients with cardiopulmonary diseases such as acute coronary syndrome, acute myocardial infarction, heart failure and pulmonary embolism [20][21][22][23][24][25][26][27]. Whereas the clinical use of cardiac troponin could not only be limited in primary cardiopulmonary diseases.…”
Section: Discussionmentioning
confidence: 99%